2010
DOI: 10.1177/156482651003100224
|View full text |Cite
|
Sign up to set email alerts
|

Across-Country Comparisons of Selected Infant and Young Child Feeding Indicators and Associated Factors in Four South Asian Countries

Abstract: Background. Information on infant and young child feeding is widely available in Demographic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 12 publications
9
66
0
1
Order By: Relevance
“…Dibley et al (2010) in their crosscountry comparison in south Asia 31 also found that rates of exclusive breastfeeding among infants for first six months were not determined by any of the infant variables (degree of prematurity, size at birth, other neonatal disorders) rather they were determined by socio-economic status, which was again similar to the findings from Flacking et al (2007). 39 This highlights the need for improved breastfeeding support for socio-economically disadvantaged mothers, during and after the hospital stay.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Dibley et al (2010) in their crosscountry comparison in south Asia 31 also found that rates of exclusive breastfeeding among infants for first six months were not determined by any of the infant variables (degree of prematurity, size at birth, other neonatal disorders) rather they were determined by socio-economic status, which was again similar to the findings from Flacking et al (2007). 39 This highlights the need for improved breastfeeding support for socio-economically disadvantaged mothers, during and after the hospital stay.…”
Section: Discussionsupporting
confidence: 72%
“…8 Also, in a cross-country comparison of data from four South Asian countries it was found that though there were no factors consistently associated with the rate of exclusive breastfeeding for first six months across countries, more ANC visits was associated with higher rates of exclusive breastfeeding in India. 31 Thus, there is evidence that antenatal care was significantly associated with exclusive breastfeeding, however, amidst the dearth of adequately powered randomized controlled trials, 32 the evidence that antenatal breastfeeding education was effective in increasing breastfeeding duration is mixed. 32e35 Nevertheless, on the basis of the available evidence, 35e37 it is likely that improving antenatal care and ensuring breastfeeding education during antenatal care could lead to better breastfeeding outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the observation in earlier study in Assam; however a study based on NFHS2 has shown delivery in the health facility to be a risk factor for not exclusively breastfed while another has reported no consistent association. 15,18 The type of facility has not been specified in the studies. The EBF rates were more for births at private institutions than home in the present study indirectly highlighting the role of staff in the government facilities in promotion of BF.…”
Section: Discussionmentioning
confidence: 99%
“…Infant and young child feeding practices in the South Asia region have not reached the expected levels that are required to achieve a substantial reduction in child mortality. 5 The prevalence of exclusively breastfeeding at 1, 3 and 6 months were 74%, 24% and 9%, and partial feeding was initiated in 15%, 38% and 79% babies, respectively in Bhaktapur district of Nepal. 6 The cultural food taboos and beliefs which are deeply rooted in some communities are found to influence…”
Section: Introductionmentioning
confidence: 92%